Korporasi Pertanggungjawaban Pidana Direktur Utama Korporasi Atas Kegiatan Usaha Bahan Kimia Yang Menimbulkan Pencemaran Lingkungan Hidup Ditinjau Dari Undang-undang Nomor 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Rakhmadiar, Derry Hadi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
It is possible that most environmental crimes involve corporations, in the sense that crimes are committed within the scope of the corporation and on behalf of the corporation. This contribution attempts to answer questions about how corporate criminal responsibility has evolved in several jurisdictions, and how this concept has been interpreted and implemented in Indonesia. contributions explain the development of corporate criminal liability, and classify them into obligations for companies and obligations for company officials. To find this out, it is necessary to investigate further to find out where the errors and criminal liability of the corporation and the management/leader of the corporation lie. In this issue, environmental crimes involving corporations and corporate management/leaders are discussed, namely whether corporate management/leaders can be subject to criminal responsibility for causing pollution in terms of Law Number 32 of 2009 concerning Environmental Protection and Management. It was found that the corporation had disposed of B3 waste without prior treatment into the sea and damaged the mangrove forest to death, its action violated Article 103 of the UUPPLH. This has prompted corporations to provide false data to investigators to avoid criminal liability, and this action has violated Article 113 of the UUPPLH. The management/leader of the corporation has the right to be responsible for environmental pollution caused by chemicals produced by the corporation based on the individual vicarious liability theory, where the corporate leader is responsible for the actions of others or the actions of the corporation, because the corporate leader is considered to have allowed or not adequately supervised the actions of the corporation. perpetrator.